Red-emitting rhodamine dyes for fluorescence microscopy and nanoscopy. - Kolmakov, K; Belov, V; Bierwagen, J; Ringemann, C; Müller, V; Eggeling, C; Hell, S (2010)
Fluorescent markers emitting in the red are extremely valuable in biological microscopy since they minimize cellular autofluorescence and increase flexibility in multicolor experiments. Novel rhodamine dyes excitable with 630 nm laser light and emitting at around 660 nm have been developed. The new rhodamines are very photostable and have high fluorescence quantum yields of up to 80 %, long excited state lifetimes of 3.4 ns, and comparatively low intersystem-crossing rates. They perform very well both in conventional and in subdiffraction-resolution microscopy such as STED (stimulated emission depletion) and GSDIM (ground-state depletion with individual molecular return), as well as in single-molecule-based experiments such as fluorescence correlation spectroscopy (FCS). Syntheses of lipophilic and hydrophilic derivatives starting from the same chromophore-containing scaffold are described. Introduction of two sulfo groups provides high solubility in water and a considerable rise in fluorescence quantum yield. The attachment of amino or thiol reactive groups allows the dyes to be used as fluorescent markers in biology. Dyes deuterated at certain positions have narrow and symmetrical molecular mass distribution patterns, and are proposed as new tags in MS or LC-MS for identification and quantification of various substance classes (e.g., amines and thiols) in complex mixtures. High-resolution GSDIM images and live-cell STED-FCS experiments on labeled microtubules and lipids prove the versatility of the novel probes for modern fluorescence microscopy and nanoscopy.